Study on Designing Sulfur Containing Bifunctional Building Block with Improved Refractive Index - G. S. Jha; P. Chhabra; G. Suri; M. Tyagi; P. Arora; G. Seshadri; R. K. Khandal (E-Journal of Chemistry)
Sulfur and chlorine containing bifunctional diols with C-S bond has been prepared starting from chloroepoxy alkane and thioalcohol. The studies of FTIR, TLC, HPLC and NMR have been used to understand the reaction mechanism, as well as for optimization of the reaction parameters. The reaction is highly exothermic and the effect of temperature, rate of addition of reagents and reaction time are important factors affecting the formation of diol. Viscosity studies, HPLC, FTIR, NMR and acid number studies have shown that, these parameters could be used as process control parameters for the synthesis of diol. Refractive index of the synthesized diol is found to be higher than that of the reactants used.